2017
DOI: 10.14807/ijmp.v8i1.521
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the determinants of housing prices

Abstract: Fundamental determinants of housing prices which affect housing demand and supply are the most common in developed countries.These are economic and financial determinants as well as demographic indicators. However, housing price analysis in less developed countries submit controversial and not sufficient results about the impact of interest rate, inflation and unemployment.Moreover, it does not investigate the influence of demographic variables and the means of economic policy. In this article the effect of GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Amongst the variables modeled in the study, the housing loan rate has the strongest impact on housing prices, whereas money supply has a negligible effect on housing prices. Cohen and Karpaviciute (2017) found that interest rate, inflation and immigration are not determining housing prices. However, GDP, unemployment, lagged value of the housing prices in the previous period and macroprudential policy’s exercise does affect housing prices in Lithuania during 2001Q1–2014Q4.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the variables modeled in the study, the housing loan rate has the strongest impact on housing prices, whereas money supply has a negligible effect on housing prices. Cohen and Karpaviciute (2017) found that interest rate, inflation and immigration are not determining housing prices. However, GDP, unemployment, lagged value of the housing prices in the previous period and macroprudential policy’s exercise does affect housing prices in Lithuania during 2001Q1–2014Q4.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GDP per capita is one of the main determinants of housing prices. GDP per capita increase leads to an increase in housing demand like other commodities and hence housing prices are increased and vice versa and has been used in the studies by Cohen and Karpaviciute (2017) and Kakar and Kakar (2011) .…”
Section: Empirical Modelmentioning
confidence: 99%
“…For example, Cesa-Bianchi et al (2015), Tsatsaronis and Zhu (2004), Glindro et al (2008) and Hofmann (2003) used several financial and macroeconomic-inclined variables in examining the drivers for housing price. Numerous studies have been done on unveiling the macroeconomics and financial determinants of housing price in the isolation form for specific countries or city level [5]: Cyprus (Alola, 2020), the USA (Mohan et al , 2019), London, the United Kingdom (Sivitanides, 2018), the United Kingdom (Holly and Jones, 1997), Lithuania (Gasparėnienė et al , 2016; Cohen and Karpavičiūtė, 2017), Greece (Panagiotidis and Printzis, 2016; Katrakilidis and Trachanas, 2012; Brissimis and Vlassopoulos, 2008), Namibia (Kaulihowa and Kamati, 2019), Norway (Anundsen and Jansen, 2013) and China (Wang and Zhang, 2014; Deng et al , 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cohen and Karpavičiūtė (2017) analyzed the data set from 2001 to 2014 and identified that approximately 99 per cent of the changes in the real estate prices in Lithuania are defined by determinants such as GDP, unemployment and introduction of macroprudential policy. Kok et al (2018) investigated macroeconomic factors influencing property prices in Malaysia and concluded that 60 per cent of changes in real estate market are explained by real GDP.…”
Section: Literature Reviewmentioning
confidence: 99%